Mother night [videorecording (DVD)] - Nolte, Nick; Lee, Sheryl; Arkin, Alan; Goodman, John, 1952-; Weide, Robert B.; Weide, Robert B.; Gordon, Keith, 1961-; Gordon, Keith, 1961-; Vonnegut, Kurt (New Line Home Video, 2000)
From his jail cell in Israel, an American playwright on trial for war crimes looks back on his life. Living in pre-World War II Berlin he becomes an allied spy within the Nazi Party. After the war, when he goes back to America, he is confronted by both Nazi haters and sympathizers.